2000
DOI: 10.2134/jeq2000.00472425002900060034x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Applications of Paper Mill Sludge in an Agricultural System: Soil Effects

Abstract: Little information exists regarding the effects of field‐scale application of paper mill sludge on soil properties. A 5‐yr field study determined the long‐term effects of land application of paper mill sludge on an agricultural soil. The goal of this study was to determine the responses of soil chemical and physical properties to multiple applications of sludge. Five rates of sludge application were tested, ranging from 0 to 225 Mg ha−1 in multiple applications under three management protocols: applied once, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Lower sludge rates resulting in lesser increases in soil organic matter in the studies of Trépanier et al (1996a) and Nemati et al (2000) may explain the less persistent effects on soil aggregation in comparison with the research of Chantigny et al (1999) and Gagnon et al (2001). Zibilske et al (2000) clearly showed that the onset and magnitude of decreased bulk density and increased aggregation of a fine sandy loam were dependent on the rate (45 to 235 Mg ha -1 ) and frequency (once, biennially, and annually) of combined sludge application.…”
Section: Soil Bulk Density and Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower sludge rates resulting in lesser increases in soil organic matter in the studies of Trépanier et al (1996a) and Nemati et al (2000) may explain the less persistent effects on soil aggregation in comparison with the research of Chantigny et al (1999) and Gagnon et al (2001). Zibilske et al (2000) clearly showed that the onset and magnitude of decreased bulk density and increased aggregation of a fine sandy loam were dependent on the rate (45 to 235 Mg ha -1 ) and frequency (once, biennially, and annually) of combined sludge application.…”
Section: Soil Bulk Density and Aggregationmentioning
confidence: 99%
“…High sludge application rates have large and persistent effects on soil organic matter while low rates of application generally result in smaller increases that are mostly detectable in the year of application. Soil organic C of a fine sandy loam remained elevated 5 yr after a single application of a combined sludge [3:1 primary:secondary (vol/vol)] at 180 and 225 Mg ha -1 , but not at rates of 45, 90, or 135 Mg ha -1 (Zibilske et al 2000). Annual or biennial applications at ≥ 45 Mg ha -1 increased soil C throughout the 5-yr study.…”
Section: Soil Organic Matter and Biological Processesmentioning
confidence: 99%
“…Available water (estimated as water held at field capacity minus that retained at permanent wilting point) is probably a more relevant factor affecting plant growth than water-holding capacity at any given water tension. Organic amendments may (e.g., Zibilske et al 2000) or may not (e.g., Gupta et al 1977) increase available water. In the latter case, incorporation increased soil water retention but most of the increase resulted from the water adsorbed by organic matter (15 MPa water).…”
Section: Water-holding Capacity and Plant Available Watermentioning
confidence: 99%
“…Along with residual past year effects, the estimated crop N availability based on the coefficients given earlier reached 412 kg N ha (1 in 2005, which is three times that supplied by PB0 and PB30 and two times that of PB60. Improved soil properties such as increased organic matter (Table 2) and its related effect on soil water availability, microbial activity and aggregation (Zibilske et al 2000;Gagnon et al 2001;Foley and Cooperband 2002;N'Dayegamiye 2006) may also be involved. Beneficial effects of several annual PB applications on corn yield have been reported (Curnoe et al 2006;N'Dayegamiye 2006).…”
Section: Crop Yieldmentioning
confidence: 99%
“…Beneficial effects of PB on crop yield and soil properties have already been reported with forage, corn, cabbage and potato (Simard et al 1998;Simard 2001;Gagnon and Ziadi 2004;Curnoe et al 2006;N'Dayegamiye 2006). However, few studies have been conducted on silage corn, despite the fact that this crop requires high N levels and may deplete soil C. Addition of PB can improve these soils, especially when applied for several years (Zibilske et al 2000).…”
mentioning
confidence: 95%